Diploid mycelia of Ustilago esculenta fails to maintain sustainable proliferation in host plant - Li, Shiyu; Yang, Mengfei; Yao, Tongfu; Xia, Wenqiang; Ye, Zihong; Zhang, Shangfa; Li, Yipeng; Zhang, Zhongjin; Song, Ruiqi (Frontiers in Microbiology, 2023)
Smut fungi display a uniform life cycle including two phases: a saprophytic phase in vitro and a parasitic phase in host plants. Several apathogenic smut fungi are found, lacking suitable hosts in their habitat. Interestingly, MT-type U. esculenta was found to maintain a parasitic life, lacking the saprophytic phase. Its long period of asexual proliferation in plant tissue results in severe defects in certain functions. In this study, the growth dynamics of U. esculenta in plant tissues were carefully observed. The mycelia of T- and MT-type U. esculenta exhibit rapid growth after karyogamy and aggregate between cells. While T-type U. esculenta successfully forms teliospores after aggregation, the aggregated mycelia of MT-type U. esculenta gradually disappeared after a short period of massive proliferation. It may be resulted by the lack of nutrition such as glucose and sucrose. After overwintering, infected Z. latifolia plants no longer contained diploid mycelia resulting from karyogamy. This indicated that diploid mycelia failed to survive in plant tissues. It seems that diploid mycelium only serves to generate teliospores. Notably, MT-type U. esculenta keeps the normal function of karyogamy, though it is not necessary for its asexual life in plant tissue. Further investigations are required to uncover the underlying mechanism, which would improve our understanding of the life cycle of smut fungi and help the breeding of Z. latifolia.